Ativos intangíveis e sua relação com desempenho e gerenciamento de resultados: uma análise à luz da regionalidade - Lopes, Fernanda Cristina Costa (2019)
The theme “intangible assets” has been appreciated by investors, shareholders, managers, researchers, among others, for your possible influence on creating value and increase organizational performance. Therefore, the following objectives were proposed in this study: (a) to analyze the relationship between intangibility and performance of Latin America companies, (b) to verify the relationship between intangibility of earnings management of Brazilian companies and (c) investigate the panorama of intangibility in the region of the triangulo minierio e alto paranaiba. For analysis of the objectives, have been applied multiple regression models with panel data and were set three intangible resources measurement perspectives, hitherto addressed jointly in a single study: representativity of the intangible asset, accounting measure of intangible, degree of intangibility and Tobin’s Q, representing economic and financial measures to determine intangibility.. Regarding objective (a), the study covered the period from 2011 to 2017 with a sample of 1,236 publicly traded companies located in the countries of Latin America, whereas Argentina, Brazil, Chile, Colombia, Mexico and Peru. The results showed the existence of relationship between intangible assets and performance of Latin American companies. In addition, the relationships were positive between the intangibility variables, degree of intangibility and Tobin's Q, and the performance variables, return on assets, profit margin and assets turnover, reinforcing the hypothesis of the higher investment in intangible assets, the greater the performance of the company. Depicting the objective (b), the sample comprised 350 Brazilian companies publicly traded in the period from 2011 to 2018. To complement this study analyzing still the influence of the level of competitiveness of the company, quality of corporate governance, ownership concentration, size and leverage on earnings management. We used the model Kang & Sivaramakrishnan (1995) as determining the metric earnings management or discretionary accruals. The results found a significant negative relationship between the representativeness of the intangible assets and earnings management and between financial leverage and earnings management. Confirmed that companies with higher proportions of intangible assets and more "leveraged" financially feature smaller indexes earnings management and, consequently, higher quality of accounting information. Regarding regionality, this study and its results support the decision-making process of the Triangulo Mineiro and Alto Paranaiba companies by reflecting the importance of intangible assets in relation to company performance and the quality of accounting information, as this region stands out for its incentive from the Minas Gerais state government and for corporate investments in intangible resources such as product innovation, process innovation, trademarks and patents.